An Objective Assessment of Men's Physical Activity during Cooper Test based on the Direct Monitoring by Accelerometer ActiGraphWGT3X - Wojciech Czarny; Jarosław Herbert; Piotr Matłosz; Maciej Śliż (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
Physical activity should play an important role at every age and on every stage of human life. It affects health, well-being and the quality of life. The authors of the paper have shown the use of accelerometer as a device for testing physical activity. They used a group of runners, who during a promoting project of physical activity called “Cooper Test for all”, applied accelerometer ActiGraph WGT3X. It was placed on the person’s waist. The use of accelerometer valuably complements the survey methods aimed at physical activity levels.